Numerical aspects of fini te elastoplasticity with isotropie ductile damage for metal forming - Saanouni, Khémais; Cherouat, Abdelhakim; Hammi, Youssef (European Journal of Computational Mechanics, 2001)
This work is devoted to the study of an efficient numerical algorithm for evaluating damaged-plastic response of a material submitted to large plastic deformations. Fully coupled constitutive equations accounting for bath combined isotropie and kinematic hardening as weil as the ductile damage are formulated in the framework of Continuum Damage Mechanics (CDM). The associated numerical aspects conceming bath the local integration of the coupled constitutive equations and the (global) equilibrium integration schemes are presented and implemented into a general purpose Finite Element code (ABAQUS). For the local integration of the Jully coupled constitutive equations an efficient implicit and asymptotic scheme is used. Special care is given to the consistent tangent stiffness mat rix derivation as weil as to the reduction of the number of constitutive equations. Sorne numerical results are presented to show the numerical performance of the proposed stress calculation algorithm and the capability of the approach to predict the damage initiation and growth during a given metalforming process.